The Quiet Hand of God : Faith-Based Activism and the Public Role of Mainline Protestantism - Evans, John Hyde, 1965-; Wuthnow, Robert (Book collections on Project MUSE., 2002)
Robert Wuthnow and John H. Evans bring together a stellar collection of essays that paints a contemporary portrait of American Protestantism--a denomination that has remained quietly, but firmly, influential in the public sphere. Mainline Protestants may have steered clear of the controversial, attention-grabbing tactics of the Religious Right, but they remain culturally influential and continue to impact American society through political action and the provision of social services.